Detection of ROS1 gene fusions using next-generation sequencing for patients with malignancy in China - Li, Ning; Chen, Zhiqin; Huang, Mei; Zhang, Ding; Hu, Mengna; Jiao, Feng; Quan, Ming (Frontiers in Cell and Developmental Biology, 2022)
Objective: This study aimed to identify ROS1 fusion partners in Chinese patients with solid tumors. Methods: Next-generation sequencing (NGS) analysis was used to detect ROS1 rearrangement in 45,438 Chinese patients with solid tumors between 2015 and 2020, and the clinical characteristics and genetic features of gene fusion were evaluated. H&E staining of the excised tumor tissues was conducted. Samples with a tumor cell content ≥20% were included for subsequent DNA extraction and sequencing analysis. Results: A total of 92 patients with ROS1 rearrangements were identified using NGS, and the most common histological type lung cancer. From the 92 ROS1 fusion cases, 24 ROS1 fusion partners had been identified, including 14 novel partners and 10 reported partners. Of these, CD74, EZR, SDC4, and TPM3 were the four most frequently occurring partners. Fourteen novel ROS1 fusion partners were detected in 16 patients, including DCBLD1-ROS1, FRK-ROS1, and VGLL2-ROS1. In many patients, the ROS1 breakpoint was located between exons 32, 34, and 35. Conclusion: This study describes 14 novel ROS1 fusion partners based on the largest ROS1 fusion cohort, and the ROS1 breakpoint was mostly located between exons 32 and 34. Additionally, NGS is an optional method for identifying novel ROS1 fusions.